Raman-IR spectroscopic, and XRD analysis of selected samples from Fogo Island, Cabo Verde: Implications for ancient Martian volcanology. Issue 11 (1st June 2023) - Aznar, M.; Sanz-Arranz, A.; Shkolyar, S.; Sawyers, E.R.; Konstantinidis, M.; Lopez-Reyes, G.; Veneranda, M.; Lymer, E.A.; Freemantle, J.R.; Daly, M.G.; Cloutis, E.A.; Rull-Perez, F.; et al.
Highlights: Chã das Caldeiras eruptions as analogue for ancient Mars. XRD, FTIR and Raman characterization of mineral phases. Fogo Island as candidate for the Planetary Terrestrial Analog Library (PTAL) Abstract: Several space missions from NASA, and ESA have visited and will land on Mars in the search for life. The last mission to arrive was the Mars 2020 Perseverance rover on 18 February 2021. The next mission to Mars will be ExoMars Rosalind Franklin rover, expected to touch down sometime after 2028. Both Mars2020 and ExoMars are equipped with Raman spectroscopic systems: SuperCam and SHERLOC on Perseverance, and Raman Laser Spectrometer (RLS) on Rosalind Franklin (RF). These instruments will be tasked with identifying rocks, minerals, and potential organic biosignatures on the Martian surface. There are many challenges associated with the qualitative and quantitative analysis of resulting data received from current missions on Mars. It is our belief that studies of new terrestrial Martian analogues can help to overcome these challenges. Here, we introduce Chã das Caldeiras Outcrop, Fogo Island, Cabo Verde as a new volcanic terrestrial analog for Mars. We sampled several areas of relevance in Chã das Caldeiras and conducted a complete band analysis of Raman spectra for targets from this site. Additional analyses included ATR-FTIR and XRD. We detected several pyroxene types (augite and diopside) and plagioclase feldspar species (orthoclase, bytownite, sanidine, albite, and anorthite), olivine (forsterite), oxides (magnetite), and leucite. The alteration and secondary minerals detected were carbonates (calcite and dolomite), oxides (goethite, anatase, and hematite), spinel (chromite), phosphate (apatite), various clays, and zeolites (chabazite and muscovite and analcime). We present the Chã das Caldeiras site as a possible new volcanic analogue for Mars given: 1) the similarities to other volcanic places in the Canary Islands; 2) the exclusive geological evolution that is only present in the volcanic emplacement from the Macaronecia-group; 3) the pristine quality of the samples from the outcrop as well as the alteration volcanic minerals.